Empowerment of Women Panchayat Members: Learning from Kerala (India) - Jos Chathukulam and M.S. John (AJWS Vol. 6 No. 4, 2000 pp. 66-101, 2000)
This study seeks to examine some initial outcomes of the incorporation of women in local governance, following the introduction of 33 percent reservation of seats for women representatives in local-level political bodies in rural areas of India in 1995. The paper is therefore based on extensive interviews with twenty seven women, who were elected members of bodies of local governance, i.e, panchayats, of Vaikom Block, in Kottayam District, Kerala, the southern-most state of India. Most of the interviewees had acquired knowledge and skills appropriate to elected office during a three-year period after assuming office, when the survey was undertaken. It was seen that these women representatives were not able to change the style and practice of the wider political arena, especially of the political parties. In fact, they found the local party machinery, especially of the Leftist parties, exercised considerable control over them, because of which they were unable to function independently or in a non-partisan manner, in dealing with development issues. The paper concludes by noting that quotas in local bodies alone are insufficient for ensuring women's political visibility. Therefore, more fundamental changes are needed for creating a more women-friendly political environment. This is particularly important for the organizations of cadre-based and supposedly progressive political parties, who, in the name of party discipline, tend to adopt means of patriarchal domination to control women panchayat members.